ENERGY OF NOVELS SAMAN, NAYLA, AND PETIR IN LITERARY PUBLISHING INDUSTRY - -, Sugiarti; Kutha Ratna, I Nyoman; Weda Kusuma, I Nyoman; Sutarto, Ayu (e-Journal of Linguistics; Vol. 4. Januari 2010 No. 1, 2010)
The research was based on the notion that novels Saman, Nayla, and Petir haveuniqueness in the exploration of ideas, narration style, and such typical techniques that creatednew esthetics. Besides, the literary works were written by three creative, innovative andknowledgeable young women who, in expressing their ideas and thoughts, were able to totallyframe story and give energy to the novels Saman, Nayla, and Petir. In the history of Indonesiancontemporary literary works, they (Ayu Utami, Djenar Maesa Ayu, and Dewi Lestari) wereknown to have produce monumental works, which in turn received good responses in Indonesianliterature publishing industry.This research is aimed at describing (a) thematic aspect and energy of the novels Saman,Nayla and Petir, which encourages literature publishing industry to publish; (b) readers’reception of the themes novels Saman, Nayla, and Petir in social and cultural change andpublishing industry; (c) relevance of cultural industry and economic praxis of readers, bookmarket and publishing industry of literary history. The research method used was descriptivewith qualitative and hermeneutic approaches. Meanwhile, the data was deeply analyzed in theunderstanding, content, and context. The analysis was conducted in cyclic and counter balancedways to gain deep understanding of writers’ thoughts, readers’ responses to the literary works,and the role of publishing industry with available market prospect. The research was based ontheory of post structuralism, reception, intertext, and cultural industry in literature.The research results showed that (1) thematic aspects and energy of the novels Saman,Nayla, and Petir as a context described women’s concern about social and cultural structure,patriarchy culture, and conflicts between traditional and modern structures. There were vulgarand jumping expressions, contrasting dictions, fantasy and symbolic language, the use of naturalstyle, free narrative, surprising and scientific techniques. The narative strength, characteristic, anduniqueness of the novel Saman, Nayla, and Petir have motivated the publishing industry topublish them ; (2) readers’ reception to the themes of the novels Saman, Nayla, and Petir inrelation to social and cultural change, and literature publishing industries in Indonesia, could becategorized into two parties, pro and contra. The socio and cultural change has caused the literaryvalues not to be bound by time and space. Such values keep growing and changing ; (3) relevanceof cultural industry and economic practice of readers’ book market and publishing industry ofliterary history, it could be seen that model became collective, business and ideological orientedinstead of other more important things. Indonesian literary history has experienced reduction as aresult of the development of cultural industry, regardless the fact that it was still based on estheticstandard.
Keywords: energy of novel, public responses, cultural industry, publishing industry